Math, asked by mithileshsahi37243, 10 months ago

give me answer I give you 15 pts​ please please please

Attachments:

Answers

Answered by TakenName
1

Answer:

x = -1/2 is the solution

Step-by-step explanation:

Given \dfrac{2x-1}{3} -\dfrac{6x-2}{5} =\dfrac{1}{3}

We use the BODMAS to solve the following

5(2x-1)-3(6x-2)=5 [Multiplication: 15 on both sides]

10x-5-18x+6=5 [Multiplication: Distribution Law]

-8x=4

x=-\dfrac{1}{2} [Division: -8 on both sides]

Answered by Anonymous
1

Answer:

Hope it helps

         

     

Attachments:
Similar questions